2020
DOI: 10.3390/md18120645
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity Potential of Marine Natural Products from Scleractinia-Associated Microbes and In Silico Anti-SARS-COV-2 Evaluation

Abstract: Marine organisms and their associated microbes are rich in diverse chemical leads. With the development of marine biotechnology, a considerable number of research activities are focused on marine bacteria and fungi-derived bioactive compounds. Marine bacteria and fungi are ranked on the top of the hierarchy of all organisms, as they are responsible for producing a wide range of bioactive secondary metabolites with possible pharmaceutical applications. Thus, they have the potential to provide future drugs again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 78 publications
(68 reference statements)
0
43
0
Order By: Relevance
“…It was found to interact with several amino acids in the active site, including Phe140, Gly143, His163, His164, Glu166, Gln189, and Thr190. Several research groups investigated synthetic and natural products for their inhibition of this target among other SARS-CoV-2 targets [36][37][38]. We have previously used the same target to investigate the potential inhibition of phytochemicals from In addition to the human NE, we were also interested in investigating the potential binding and inhibitory activities of isolated compounds against SARS-CoV-2 main protease (M pro ) owing to the current pandemic situation.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…It was found to interact with several amino acids in the active site, including Phe140, Gly143, His163, His164, Glu166, Gln189, and Thr190. Several research groups investigated synthetic and natural products for their inhibition of this target among other SARS-CoV-2 targets [36][37][38]. We have previously used the same target to investigate the potential inhibition of phytochemicals from In addition to the human NE, we were also interested in investigating the potential binding and inhibitory activities of isolated compounds against SARS-CoV-2 main protease (M pro ) owing to the current pandemic situation.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…From coral-associated organisms, 300 biologically active substances with cytotoxic, antiparasitic, antibacterial, antiinflammatory activities have been isolated (Hou et al, 2019). These compounds are studied as potential anti-tumour and antiviral preparations, including against SARS-CoV-2 and HIV (El-Hossary et al, 2020;Zahran et al, 2020). Many bioactive products (terpenoids, sesquiterpenes, diterpe-nes, steroids and many other) are produced by soft corals and are promising objects for the development of various pharmaceutical preparations (Sang et al, 2019).…”
Section: Marine Organisms Producing Cytotoxic Compoundsmentioning
confidence: 99%
“…Furthermore, many studies have shown that several marine metabolites isolated from scleractinia related organisms, sponges and algae can interact with the main protease of Sars-CoV-2, M pro [ 13 , 14 , 15 , 26 , 27 , 28 ]. M pro is a crucial protein enzyme of the virus and has a critical role in mediating the replication and transcription of the viral particles, making it a potential drug target against the virus [ 27 , 28 , 29 ]. As depicted by Figure 1 , several marine metabolites such as phycocyanbillins were found to bind to RNA dependent RNA polymerase (RdRp) with equivalent or higher potency than Remdesivir, making them advantageous over standard therapy [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%